Evaluación de la producción de energía eléctrica en una pila de combustible microbiana a partir aguas residuales de la industria de cerveza artesanal a escala de laboratorio, empleando E. Coli y Pseudomonas Aeruginosa (2018)
This research project focuses on the evaluation of the production of electricity with wastewater from Colombian industry, which will be used as a substrate in a microbial fuel cell, due to the characteristics of the process. the right conditions for microorganisms, which have the capacity to generate electrical current through the degradation of organic matter through their metabolic pathways, produce electrical energy inside a PCM and at the same time there is a reduction in the contaminant load present in wastewater used as a substrate. In the first place, according to the methodology established for the research, the most relevant physicochemical properties to be evaluated in wastewater were established so that this would present favorable conditions for the growth of microorganisms, which are: pH, chemical oxygen demand , total solids, total suspended solids and the conductivity of the water, in the same way, establish if there was the presence of native microorganisms.